Cinema as theoretical elucidation: studies on Bauman in I, Daniel Blake (Research, Society and Development, 2022)
This paper composes a series of theoretical studies which bring some movies closer to the book Liquid Modernity, by Zygmunt Bauman, Polish sociologist; in this text, ananalys is of the film I, Daniel Blake Will be presented, taken as representative of the chapter named Work of the aforementioned work. The article aims to establish a connection between cinematographic language and sociologist studies, in addition to advocating for the use of cinematographic works in classes of different courses and levels, aiming at the aesthetic experience as a formative possibility of being in the world. As a methodology for analyzing the film, textual and content analysis were used, through chosen frames. As a result of the analysis, it can be observed that the film can be taken as a metaphor for the Work chapter, which facilitates its theoretical understanding, when it addresses issues such as informal work and people Who find themselves thrown out of the world of work and state protection systems.